2016
DOI: 10.1186/s12958-016-0144-2
|View full text |Cite
|
Sign up to set email alerts
|

Flutamide induces alterations in the cell-cell junction ultrastructure and reduces the expression of Cx43 at the blood-testis barrier with no disturbance in the rat seminiferous tubule morphology

Abstract: BackgroundPresent study was designed to establish a causal connection between changes in the cell-cell junction protein expression at the blood-testis barrier and alterations in the adult rat testis histology following an anti-androgen flutamide exposure. Particular emphasis was placed on the basal ectoplasmic specialization (ES) in the seminiferous epithelium and expression of gap junction protein, connexin 43 (Cx43).MethodsFlutamide (50 mg/kg body weight) was administered to male rats daily from 82 to 88 pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…The question arises whether adipokines may modulate Leydig cell functioning through a mechanism that has not yet been defined. It is worth adding that our previous morphometric analysis [ 40 ] revealed a marked increase of interstitial volume, accompanied by a decreased number of Leydig cells per 1 mm 2 of the interstitial space, indicating the occurrence of Leydig cell hypertrophy after flutamide exposure. Elucidation of whether a compensatory mechanism within Leydig cells exists will require further study at the ultrastructural level.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The question arises whether adipokines may modulate Leydig cell functioning through a mechanism that has not yet been defined. It is worth adding that our previous morphometric analysis [ 40 ] revealed a marked increase of interstitial volume, accompanied by a decreased number of Leydig cells per 1 mm 2 of the interstitial space, indicating the occurrence of Leydig cell hypertrophy after flutamide exposure. Elucidation of whether a compensatory mechanism within Leydig cells exists will require further study at the ultrastructural level.…”
Section: Discussionmentioning
confidence: 79%
“…As has been stated in the introduction, short-term flutamide exposure influences morpho-functional aspects of spermatogenesis in the rat [ 40 , 45 ]. On the other hand, it has been shown that AR-mediated androgen signalling plays an important role in male metabolism by affecting the energy balance [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies, using flutamide as a antiandrogen, describe that it affects the expression of junction proteins and junction complex structure, not only by inhibiting androgen receptor activity, but also by modulating protein kinase‐dependent signaling in testicular cells (Chojnacka et al, 2016; Hejmej & Bilinska, 2018). As expected, the epididymis is also affected by flutamide exposure, with increased epididymal cells apoptosis, lower androgen receptor expression, concomitant with decreased Cx43 (gap junction protein connexin43; Lydka et al, 2011).…”
Section: Discussionmentioning
confidence: 99%